Calitz, Talita M.L. (2019). Enhancing the Freedom to Flourish. London, U.K.: Routledge (Journal of Student Affairs in Africa, 2021)
It is evident that, whatever the country and system, some students benefit from highereducation more than others. Talita Calitz addresses the problem of equal participation with conceptual clarity and practical proposals which have global relevance. In my view, the outstanding achievement of her book is to replace the usual deficit view of students whose economic and social circumstances make it difficult for them to benefit from university education with a theory of participation which emphasises agency and inclusion. This achievement results from Calitz's combining a human development approach with insight from the life stories of eight students in a South African university who faced economic and academic barriers to equal participation.